Comparing Silicon and Diamond Micro-cantilevers Based Sensors for Detection of Added Mass and Stiffness Changes. (2015) - Possas, M.; Rousseau, L.; Ghassemi, F.; Lissorgues, G.; Gonzales, P.; Scorsone, E.; Bergonzo, P.
Abstract: In this work, silicon and diamond cantilevers based sensors have been designed and fabricated on five different geometries. Parylene homogeneous nanolayers have been deposited over the sensors in order to evaluate the performance of each design. Silicon and diamond have been compared as building materials for resonant sensors and the corresponding shifts on resonance frequency and quality factor have been recorded. A model is further introduced to disentangle the effect of added mass and rigidity changes. We demonstrate the sensitivity of our sensor to mass effect for low mass deposition and the diamond cantilevers exhibit a three times higher sensitivity as compared to silicon cantilevers for the same geometry.